Implementasi Metode Simple Exponential Smoothing Winter’s Untuk Memprediksi Pakan Ternak - Faozanolo Lafau (Graha Mitra Edukasi, 2023)
So far, production has been carried out based on warehouse stock. Where production continues regardless of sales demand. This can result in losses if the number of sales requests is less than the production results so that there are unsold products left, or if there are sales requests that exceed stock so that PT. Satwa Karya Prima was unable to fulfill the request. This is due to the inaccuracy of sales requisition data due to manual recording. To overcome this problem, a new system is needed to improve the current system. From the test results, the software created is able to find out the amount of stock required, the estimated number of sales requests, forecasting results using the Simple Exponential Smoothing and Winter's methods of production each month and production results. It is hoped that using the Simple Exponential Smoothing and Winters Methods can overcome smaller production estimation errors with minimum error values.